PENGARUH PENGETAHUAN INVESTASI, EXPECTED RETURN, DAN KEMAJUAN TEKNOLOGI TERHADAP MINAT INVESTASI DI PASAR MODAL: (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Budi Luhur) - Putri Lestari; Sugeng Priyanto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research is based on students' interest in investing. The aim of this research is that researchers want to find out whether investment knowledge, expected returns and technological advances have an influence on investment interest. The population of this study were students from the economics and business faculty at Budi Luhur University with a sample of 100 respondents using data collection techniques through questionnaires. The data analysis method in this research is multiple linear regression analysis. The results of this research show that expected return have an effect on investment interest, while investment knowledge and technological advances have no effect on investment interest.